The Synthesis, In Vitro Bio-Evaluation, and In Silico Molecular Docking Studies of Pyrazoline-Thiazole Hybrid Analogues as Promising Anti-α-Glucosidase and Anti-Urease Agents - Yousaf Khan; Shoaib Khan; Rafaqat Hussain; Aneela Maalik; Wajid Rehman; Mohamed W. Attwa; Rafia Masood; Hany W. Darwish; Hazem A. Ghabbour (MDPI AG, 2023)
In the present work, a concise library of benzothiazole-derived pyrazoline-based thiazole (1-17) was designed and synthesized by employing a multistep reaction strategy. The newly synthesized compounds were screened for their α-glucosidase and urease inhibitory activities. The scaffolds (1-17) were characterized using a combination of several spectroscopic techniques, including FT-IR, 1H-NMR, 13C-NMR, and EI-MS. The majority of the synthesized compounds demonstrated a notable potency against α-glucosidase and urease enzymes. These analogues disclosed varying degrees of α-glucosidase and urease inhibitory activities, with their IC50 values ranging from 2.50 to 17.50 μM (α-glucosidase) and 14.30 to 41.50 (urease). Compounds 6, 7, 14, and 12, with IC50 values of 2.50, 3.20, 3.40, and 3.50 μM as compared to standard acarbose (IC50 = 5.30 µM), while the same compounds showed 14.30, 19.20, 21.80, and 22.30 comparable with thiourea (IC50 = 31.40 μM), respectively, showed excellent inhibitory activity. The structure−activity relationship revealed that the size and electron-donating or electron-withdrawing effects of substituents influenced the enzymatic activities such as α-glucosidase and urease. Compound 6 was a dual potent inhibitor against α-glucosidase and urease due to the presence of -CF3 electron-withdrawing functionality on the phenyl ring. To the best of our knowledge, these synthetic compounds were found to be the most potent dual inhibitors of α-glucosidase and urease with minimum IC50 values. Moreover, in silico studies on most active compounds, i.e., 6, 7, 14, and 12, were also performed to understand the binding interaction of most active compounds with active sites of α-glucosidase and urease enzymes.